2007
DOI: 10.1111/j.1601-5215.2007.00208.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies of caloric vestibular stimulation: implications for the cognitive neurosciences, the clinical neurosciences and neurophilosophy

Abstract: CVS can be used to investigate various cognitive phenomena including perceptual rivalry, attention and mood, as well as somatosensory representation, belief, hemispheric laterality and pain. The technique can also be used to investigate clinical conditions related to these phenomena and may indeed have therapeutic utility, especially with respect to postlesional disorders, mania, depression and chronic pain states. Furthermore, we propose that based on existing reports of the phenomenological effects of CVS an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 252 publications
(289 reference statements)
3
63
0
Order By: Relevance
“…6 It was reported that long term exposure to cold decreases T3 and T4 levels. 16 Our study agree with these results as we have observed decrease in the T3 and T4 levels followed by forced cold water swimming stress. However vestibular stimulation by hot and cold water effectively prevented this stress induced fall in thyroid hormone secretion.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…6 It was reported that long term exposure to cold decreases T3 and T4 levels. 16 Our study agree with these results as we have observed decrease in the T3 and T4 levels followed by forced cold water swimming stress. However vestibular stimulation by hot and cold water effectively prevented this stress induced fall in thyroid hormone secretion.…”
Section: Discussionsupporting
confidence: 83%
“…14 Caloric vestibular stimulation: The middle ear cavity was irrigated with hot (40 degree centigrade) or cold (15 degree centigrade) water through a polyethylene tube for 15 days. 15,16 Study design: The present study is an experimental study. T3, T4, Cholesterol levels and body weight were recorded before and after vestibular stimulation by standard methods.…”
Section: Methodsmentioning
confidence: 99%
“…The description of the anatomy and function of the vestibular cortex is thus not only necessary for systems neuroscience, but should also further our understanding of clinical aspects of vestibular disorders and the role of the vestibular cortical system in perception, cognition, and consciousness. The vestibular system has been involved in a variety of perceptive and cognitive functions based on behavioral effects reported after caloric or galvanic vestibular stimulation in healthy humans (Lenggenhager et al, 2008;Lopez and Blanke, 2007;Lopez et al, 2010b;Miller and Ngo, 2007), and such stimulation may have beneficial effects on deficits regarding external and corporeal space in brain-damaged patients (Bottini et al, 1995;McGeoch et al, 2008;Vallar et al, 1993).…”
Section: Summary and Future Perspectivesmentioning
confidence: 99%
“…For these tasks, the vestibular system does not operate in isolation but strongly interacts with the somatosensory and visual systems (Angelaki & Cullen, 2008). Despite the importance of vestibular signals for coding one's own body location with respect to the environment, little is known about its contribution to the mechanisms of self-consciousness (see recent reviews in Lenggenhager, Smith, & Blanke, 2006;Lopez & Blanke, 2007;Lopez, Halje, & Blanke, 2008;Miller & Ngo, 2007). Yet, several neurological observations suggest a vestibular contribution to bodily self-consciousness (Bisiach et al, 1991;Blanke, Landis, Spinelli, & Seeck, 2004;Blanke, Ortigue, Landis, & Seeck, 2002;Hécaen & de Ajuriaguerra, 1952;Ramachandran & McGeoch, 2007;Rode et al, 1992;Schiff & Pulver, 1999;Vallar, Bottini, Rusconi, & Sterzi, 1993).…”
Section: Introductionmentioning
confidence: 99%